CO2 capture and amine solvent regeneration in Sotacarbo pilot plant. (1st November 2017) - Deiana, Paolo; Bassano, Claudia; Calì, Gabriele; Miraglia, Paolo; Maggio, Enrico
Abstract: The removing CO2 from fossil fuel based power plants has got increased interest due to environmental reasons. CO2 absorption by chemical solvents is an attractive and commercial applicable CO2 capture technology. In that field ENEA, together with Sotacarbo, is developing different activities on their pilot plants to test the use of gasification technologies for the combined production of hydrogen and electric power in medium and small scale commercial plants and to test CO2 absorption and regeneration technologies. This paper reports the first results achieved during preliminary experimentations carried out to assess the CO2 absorption performance with monoethanolamine. Different plant operating conditions have been tested. The absorption CO2 efficiency has been evaluated and the main parameters of the regeneration process are discussed.